Knowledge, attitudes, and practices of adolescents regarding sexuality and reproductive issues in the Cordillera administrative region of the Philippines - Pasay-an, Eddieson; Magwilang, Judith Odanee G; Pangket, Petelyne P (UI Scholars Hub, 2020)
Background: This study investigates the knowledge, attitudes, and practices (KAP) concerning reproductive health (RH) and sexuality among in- and out-of-school adolescents in the Cordillera Administrative Region (CAR), Philippines. Methods: Using a quantitative, cross-sectional approach, this study examined 739 in- and out-of-school adolescents who were recruited through snowball and simple random sampling. Results: Statistically significant differences were noted in the knowledge, attitudes, and practices regarding sexuality based on age. Age was associated with knowledge, attitudes, and practices concerning RH. Educational attainment toward sexuality also caused statistically significant changes in knowledge, attitudes, and practices. The KAP regarding sexuality and sex only showed statistically significant differences in attitudes and RH and sex to attitudes. Schooling produced statistically significant differences in knowledge, attitudes, and practices regarding sexuality; for RH, statistically significant differences were found only in knowledge and attitudes. Conclusion: The results can inform educational campaign development, which can be used when devising appropriate behavioral change materials suitable for and responsive to the needs and demands of the CAR adolescents.